Pelatihan Penggunaan Kuesioner Usability untuk Pengukuran Kualitas Perangkat Lunak bagi Mahasiswa dan Masyarakat Umum: Training on the Use of Usability Questionnaire for Measuring Software Quality for Students and the General Public - Wahyuningrum, Tenia; Martono, Galih Hendro; Wardhana, Helna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Agile development ensures quality software is on time and according to user expectations. Therefore, software testing is essential before launch, including usability testing as part of the user experience. However, the many choices of questionnaires in usability testing make it difficult for developers to determine the appropriate method. This community service is a training activity that aims to improve the understanding of students and the general public, especially those involved in software development related to usability testing. The training is conducted face-to-face with counseling, namely interactive lectures, discussions, case studies, and quizzes. The training materials include an introduction to software quality and usability evaluation, respondent selection techniques, an introduction to types of usability questionnaires, and exercises in calculating and interpreting usability scores using the Usability Metric for User Experience (UMUX-Lite) questionnaire. The training results showed that the level of understanding was still low (31.07%); this result was due to several obstacles, namely the imbalance in the number of participants and facilitators, the relatively short discussion time, and not all participants being active in the activities. The strategy for future improvements is to conduct remedial sessions, re-evaluate learning methods and media, and divide participants into small groups with adequate training facilitators.